Budaya indonesia sebagai identitas nasional indonesia - Andi Aco Agus (Jurnal Ekonomi dan Riset Pembangunan, 2026)
This study aims to determine why foreign citizens are interested in Indonesian culture, how Indonesian culture has developed in the eyes of the world, and how Indonesia maintains culture as a national identity. The research method used is descriptive research with library research. Research activities are carried out by collecting information and data with the help of various existing materials. The results of the study indicate that Indonesian national identity traits are the characteristics or distinctive of the Indonesian people that distinguish them from other nations in the world. We can see these characteristics from the daily behavior of Indonesian people in general and also the culture and unique attributes possessed by the Indonesian people, so that Indonesian culture can be used as a benchmark for the national identity of a nation, namely Indonesia. The main attraction of Indonesian culture for foreign citizens lies in the diversity and unique characteristics contained in its cultural elements, namely dance, song, and traditional clothing. At the international level, Indonesian culture has received good acceptance, evidenced by the high enthusiasm in cultural promotion activities abroad.